Jenis-Jenis Balanophoraceae Di Sumatera Barat - Rizky Paramita Mukhti; - Syamsuardi; - Chairul (Universitas Andalas, 2012)
The study of Balanophoraceae in West Sumatra has been conducted from January to May 2012. This study used observation and direct collection method at seven locations in West Sumatra and continued in Herbarium Andalas University (ANDA). The result indicated that three spesies of Balanophora (B. elongata, B. indica, and B.dioica) were identified. B. elongata has 9 female individuals, B. indica has 2 male individuals and 1 female individual, B. dioica 1 male individual and 1 female individual. The tuber was significant character to distinguish three studied spesies of Balanophora. B. elongata and B. dioica had a branched tuber but no branched tuber was detected in B. indica. The leaf color and the type of inflorescence were also valuable characters to differ between these species. It was assumed that most of the Balanophora species were found in habitat where the precipitation is 2500-5000 mm/year along mountain rain forest in Sumatra.Keywords: spesies, Balanophora, character, habitat, west sumatra